Functional and hemodynamic results after transcatheter mitral valve leaflet repair with the PASCAL device depending on etiology in a real-world cohort. Issue 6 (December 2021) - Barth, Sebastian; Shalla, Alaa; Kikec, Jan; Kerber, Sebastian; Zacher, Michael; Reents, Wilko; Lehmkuhl, Lukas; Foldyna, Borek; Halbfass, Philipp; Lüsebrink, Ulrich; Hautmann, Martina B.
Highlights: High success rate. At 7 months, sustained mitral regurgitation reduction in functional mitral regurgitation (FMR) and degenerative mitral regurgitation (DMR) using the PASCAL system. Functional and hemodynamic improvement in FMR and DMR at follow-up. Abstract: Background: The PASCAL system (Edwards Lifescience, Irvine, CA, USA) is a novel device for edge-to-edge treatment of mitral regurgitation (MR). The aim of our study was to examine the functional and hemodynamic outcome after repair of functional (FMR) and degenerative mitral regurgitation (DMR) using the PASCAL system in a real-world setting. Methods: A total 92 consecutive patients with symptomatic MR 3+/4+ were treated in our institute using the PASCAL device. Primary endpoints included procedural success, clinical success, and major adverse event rate at 30 days and 7 months. Results: 68.5% had a functional and 31.5% a degenerative etiology. Overall success rate was achieved in 97.8% patients (98.4% FMR, 96.6% DMR). At follow-up, 85.7% of the patients (89.2% FMR, 78.3% DMR) had MR grade ≤ 1. 96.4% (97.4% FMR, 94.4% DMR) were in New York Heart Association class I or II. Six-minute walking distance improved by 96 m (92 m FMR, 106 m DMR), Kansas City Cardiomyopathy Questionnaire improved by 19 points (19 points FMR, 19 points DMR). Pro-B-type natriuretic peptide (proBNP) levels decreased from 4673 to 2179 pg/dl (5239–2018 pg/ml FMR, 3418–2530 pg/ml DMR) and mean pulmonary capillary wedge pressure from 21 to 16 mmHg (21–17 mmHg FMR, 19–13 mmHg DMR). At 30 days, there was 1 cardiovascular death (1.2%) with DMR. At 1 year, Kaplan-Meier survival was 86% (86% FMR, 86% DMR). Conclusions: Severe MR can successfully and safely be treated with the PASCAL device regardless of etiologies. This interventional approach resulted in a sustained MR reduction, improvement in exercise capacity, quality of life, proBNP levels, and hemodynamics in FMR and DMR at follow-up. Graphical abstract: Image, graphical abstract